Physical–Mechanical Properties and Dimensions of Cotton Rows - Abdualiev, Nuriddin Khabibovich; Egamov, Nodirbek Murodillaevich; ogli Juraev, Akram Azamat (RA Journal of Applied Research, 2022)
Studying the physical–mechanical properties of the soil is one of the important issues when basing the parameters of the device that softens the knot between cotton rows. At the same time, it is necessary to determine these properties when studying the effect of the device on energy and quality indicators. The physical, mechanical and technological properties of the soil (soil moisture, density and hardness) were studied in 0–15 cm layers at intervals of 5 cm according to GOST 20915–2011. It can be seen that the physical and mechanical parameters of the soil increase as its depth increases. It was determined that soil moisture in the range of 0-15 cm varies in the range of 14.8–24.0% hardness, 0.13–0.38 MPa, and density in the range of 0.86–1.05 g/cm3. The moisture of the soil corresponds to the agrotechnical requirements for processing between rows of cotton.